DE UMA CRISE A OUTRA, DE UM DARWINISMO A OUTRO: A IMPLANTAÇÃO DA PROGRESSÃO CONTINUADA NO ESTADO DE SÃO PAULO - MORAIS JUNIOR, VICENTE DE PAULO (2015)
This paper investigates the implementation of the regime of continued progression in the public schools of São Paulo in 1998, so has the research axis and reflections public policy of continued progression and the process of deployment and implementations. There was the use of two lines of research: bibliographical research and research and analysis of official deploys the regime cited, but also the gradation of the laws and their characteristics. The central research support relies on two established works, “The Structure of Scientific Revolutions” and “The Origin of Species” by Thomas Kuhn and Charles Darwin, respectively. The works cited are entitled to the title of this work, which uses the discussions proposed by Kuhn on ‘crisis’, having this as one of guidelines to analyze pre and post implementation of the combined regimen of Darwinim, which here is called teaching Darwinism. To establish a connection between the central object of research and the works mentioned above to research and discuss topics directly related, such as ‘a river and its tributaries’. The ‘affluent’ researched and discussed were: pedagogy and science, grading system, Darwinism, metaphor, public policy, gradation of the laws, identify, resistance and withdrawal. The ‘affluent’ were not restricted to literature, it was necessary to also in official discourse perform this methodological approach. The survey revealed that, as of Kuhn’s contributions of the regime of continued progression in the public schools of São Paulo only made educations in the state get out of a crisis, and to enter into another. In addition, also showed thar the teaching Darwinism that prevailed in the ranking system, chances face the regime of continued progression, but still active, now directly affecting teachers, who actively resisted or opposed, or give up, either announced or covertly.